Serum 25-hydroxyvitamin D concentrations in obese and non-obese women with polycystic ovary syndrome - (:unkn) unknown (SPRINGER HEIDELBERG, 2009)
To investigate the correlation between serum 25-hydroxyvitamin D (25-OH-VD) concentrations and metabolic parameters in obese and non-obese women with polycystic ovary syndrome (PCOS). One hundred women with PCOS were divided into two groups, obese and non-obese, according to their body mass index (BMI). Waist-to-hip ratio (WHR), Ferriman-Gallwey score, homeostasis model assessment of insulin resistance (HOMA-IR), total cholesterol, triglycerides, calcium, 25-OH-VD, LH/FSH, total testosterone, and DHEAS were measured. The serum 25-OH-VD mean levels were 56.31% lower in the obese PCOS patients. There was an association of increased HOMA-IR, BMI, WHR, triglycerides, total testosterone, and DHEAS with decreased 25-OH-VD concentrations in the obese PCOS patients. Low serum 25-OH-VD concentrations result from the presence of obesity and insulin resistance. However, the dependency between PCOS and hypovitaminosis D is questionable. Hypovitaminosis D should be kept in mind while managing obese women with PCOS.
Keywords: Polycystic ovary syndrome; 25-Hydroxyvitamin D; Insulin resistance; Obese; Non-obese; INSULIN-RESISTANCE; VITAMIN-D; HYPOVITAMINOSIS-D; GLUCOSE-TOLERANCE; PREVALENCE; IMPACT; HYPERANDROGENISM; D-3